“A Tale of a Woman and a Robe”: Institutional Criticism of the Israeli Rabbinical Establishment—The Art of Nurit Jacobs Yinon - Sperber, David (Journal of feminist studies in religion, 2021)
The project A Tale of a Woman and a Robe, initiated and produced by Israeli Jewish Orthodox video artist Nurit Jacobs Yinon in 2013, served to generate activism aimed at bringing about reform, in a particularly powerful case of feminist activism in contemporary Israeli art. This article explores the reception of the project and its critique of the Israeli patriarchal rabbinical court in the ritual immersion ceremony of female converts before three male judges. By studying the reception of the project within Jewish Orthodox communities and analyzing it in light of activist strategies utilized in Israeli Orthodox feminism, Sperber demonstrates how the artist seeks real social engagement, reaching beyond the walls of the museum or the gallery to generate a critical discourse that has the power to foment real change in the social reality.